The Lübeck flowchart for functional and aesthetic rehabilitation of aural atresia and microtia - Frenzel, Henning; Schönweiler, Reiner; Hanke, Frauke; Steffen, Armin; Wollenberg, Barbara (Otology & neurotology, 2012)
Current strategies for functional rehabilitation of microtia-atresia patients with bone-anchored implants or surgical atresia repair have been extended by the feasibility of active middle ear implants. The aim of the present research is to evaluate a new flowchart of the treatment of these patients that considers active middle ear implants. Congenital aural atresia and microtia. Bilateral cases are provided with a conductive hearing aid after birth and implanted with an active middle ear implant within the second year. Unilateral cases are provided with a conductive hearing aid and implanted with a middle ear or bone-conduction device in early childhood. Unilateral cases without amplification in the vulnerable time after birth are carefully selected for late implantation. At age 8 to 10, the auricular reconstruction is completed. Feasibility of implantation irrespective of age, functional gain in audiometry. The results of early implantation are as good as those previously published for adolescents. Mean reaction threshold with the Vibrant Soundbridge was 21 dB. Mean functional gain was 48 dB. The local tissues are unaltered and ready for auricular reconstruction. Active middle ear implants allow early and selective stimulation of the auditory pathway in children with congenital conductive hearing loss and are expected to lead to the normal development of the binaural hearing functions. To date, it is the only option if the stimulation is to be started at the age of 12 to 18 months. This was implemented into a new flowchart for aural atresia-microtia.